2017
DOI: 10.1093/abm/kax022
|View full text |Cite
|
Sign up to set email alerts
|

Fitbit step counts during inpatient recovery from cancer surgery as a predictor of readmission

Abstract: Background Postoperative ambulation is encouraged to promote timely recovery but is rarely monitored objectively or examined as a predictor of clinical outcomes, despite growing availability of wearable devices that allow passive quantification and remote real-time monitoring of the number of steps taken during recovery. Purpose To determine whether the number of steps taken during inpatient recovery predicts 30- and 60-day readmission risk after metastatic cancer surgery. Methods Patients diagnosed with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 16 publications
2
82
1
Order By: Relevance
“…During outpatient chemoradiation therapy, lower levels of activity as measured with Garmin devices were associated with greater hospitalization risk, lower likelihood of completing treatment without delays, and shorter survival 27 , 28 . In a sample of 71 patients undergoing surgery for advanced abdominal cancer, lower Fitbit step counts during inpatient recovery were associated with greater risk of unplanned 30- and 60-day hospital readmission 29 . A study of 20 abdominal cancer patients reported that daily step count on postoperative day 7 inversely correlated with postoperative complication index 30 .…”
Section: Consumer Wearable Devices In Oncology Researchmentioning
confidence: 95%
“…During outpatient chemoradiation therapy, lower levels of activity as measured with Garmin devices were associated with greater hospitalization risk, lower likelihood of completing treatment without delays, and shorter survival 27 , 28 . In a sample of 71 patients undergoing surgery for advanced abdominal cancer, lower Fitbit step counts during inpatient recovery were associated with greater risk of unplanned 30- and 60-day hospital readmission 29 . A study of 20 abdominal cancer patients reported that daily step count on postoperative day 7 inversely correlated with postoperative complication index 30 .…”
Section: Consumer Wearable Devices In Oncology Researchmentioning
confidence: 95%
“…The Fitbit is shown to be useful in other fields of medicine as well. Higher Fitbit step counts during inpatient recovery can predict lower readmission rates after metastatic peritoneal cancer surgery [16]. The Nike + FuelBand was used in one study [24] and has shown to be effective because of its ability to visualize the progress toward daily activity goals.…”
Section: Expert Opinionmentioning
confidence: 99%
“…1 week), commonly using accelerometer-based measures of physical activity, during the 6-to 12-month postoperative period [2,3]. While there has been some interest in using commercial wearable devices to describe postoperative behavior, the currently available research has been limited in scope, typically bound to short observation windows and/or only focused on assessing daily physical activity behavior in the form of daily total steps [4][5][6][7][8][9]. Our current understanding of the changes in postoperative behavior and physiology may not reflect the true relationship between these changes and outcomes of interest such as successful weight loss, adverse event incidence, and resolution of obesity-related medical comorbidities.…”
Section: Introductionmentioning
confidence: 99%